Parental Approach to Accompanying Children's Learning in the Family in RW II, Parak Gadang Timur Sub-District, Padang Timur District, Padang City - Annisa Ayu Defita; Jamaris Jamaris (Universitas Negeri Padang, 2023)
At this time, children really need to be given special attention in studying at home, because children are often engrossed in their own world, such as playing with friends, watching television, using gadgets, so often if parents don't monitor their children, children will forget. to study at home. Especially now that students are required to study from home. Therefore, various approaches are needed so that children want to obey what their parents say. Research using qualitative research that seeks to interact with research subjects naturally or naturally. The case study approach that researchers use is to find out about the parental approach in accompanying children in family learning in RW II, Parak Gadang Timur Village, Padang Timur District, Padang City. In the research conducted, there are several parental approaches in accompanying children's learning in families where parents act as educators and children as students at home. This is because the family is the center of children's education from an early age.Keywords: Parental approach, Child, Study